El sistema de control interno en la gestión de tesorería de la Dirección Regional de Transportes y Comunicaciones de Loreto 2021 - Ríos García, Amelia (2022)
This research work has been formulated with the purpose of evaluating and determining the level of implementation of the Internal Control System and its effect on the administration and management of the financial resources delegated to the Treasury Area of the Regional Directorate of Transport and Communications of Loreto during the year 2021, this institution is responsible for conducting and guiding land, water and communications transportation, as well as developing and executing road infrastructure works that contribute to the well-being and better quality of life of the population of Loreto. The research is of Quantitative type, Substantive-Descriptive level and Non-experimental design. After obtaining the data through the application of two surveys and the Kuder-Richardson reliability analysis KR-20 and KR-21, it´s concluded that during the analyzed period the Internal Control System doesn´t present any correlation with the Management of Treasury at the institution, for which a Spearman Rho correlation coefficient -0.329 was obtained, and a p > t value of 0.387 that shows statistical non-significance (α = 0.05). Likewise, when individually analyzing each of the factors that make up the Internal Control System variable, it was obtained that Organizational Culture, Risk Management and Supervision do not correlate with the Treasury Management variable, because in each case the value p > t is greater than the chosen level of significance (α = 0.05).